Upaya Pencegahan Penyebaran Covid-19 dan Usaha Mikro dan Kecil (UMK) Kelurahan Mambulau Kabupaten Kapuas Kalimantan Tengah - Aldy Juarnicko; Amalia Khairunnisa; Nadia Desyta Ramadani; Sugeng Mashabhi; Ahmad Mujaffar (Yayasan Literasi Sains Indonesia, 2022)
Thematic Real Work Lecture (KKN-T) is a form of implementation of an independent campus. Through this KKN-T activity, it seeks to improve the competence and role of students as agents of change in society, foster a spirit of volunteerism and be able to be responsible for the community. The implementation of KKN-T for the Mambulau village group was carried out in Mambulau Village, Kapuas Hilir District, Kapuas Regency, Central Kalimantan. The approach used in community service activities is participatory action research (PAR). The method of implementing KKN-T is carried out through posyandu and immunization activities, and counseling on the dangers of COVID-19 to the community. Supported by village officials and RT heads. The work program